Benthic nematode assemblage composition and diversity during a natural recovery process of Zostera noltii seagrass beds, - Materatski, P. (2017)
In 2008, the stable seagrass beds of the Mira estuary (SW Portugal) disappeared completely; however, during 2009, they have begun to present early symptoms of natural recovery, characterised by a strongly heterogeneous distribution. This study was designed to investigate the spatial and temporal variability patterns of species composition, densities and trophic composition of the benthic nematode assemblages in this early recovery process, at two sampling sites with three stations each and at five sampling occasions. Because of the erratic and highly patchy seagrass recovery and the high environmental similarity of the two sampling sites, we expected within-site variability in nematode assemblages to exceed between-site variability. However, contrary to that expectation, whilst nematode genus composition was broadly similar between sites, nematode densities differed significantly between sites, and this between-site variability exceeded within-site variability. This may be linked to differences in the Zostera recovery patterns between both sites. In addition, no clear temporal patterns of nematode density, trophic composition and diversity were evident.